Trace Element Behavior in Methane‐Rich and Methane‐Free Groundwater in North and East Texas. Issue 5 (30th October 2017) - Darvari, Roxana; Nicot, Jean‐Philippe; Scanlon, Bridget R.; Mickler, Patrick; Uhlman, Kristine
Abstract: There is concern about adverse impacts of natural gas (primarily methane) production on groundwater quality; however, data on trace element concentrations are limited. The objective of this study was to compare the distribution of trace elements in groundwater samples with and without dissolved methane in aquifers overlying the Barnett Shale (Hood and Parker counties, 207 samples) and the Haynesville Shale (Panola County, 42 samples). Both shales have been subjected to intensive hydraulic fracturing for gas production. Well clusters with high dissolved methane were previously found in these counties and are thought to be of natural origin. Overall, groundwater in these counties is of excellent quality with typically low elemental concentrations. Several statistical analyses strongly suggest that most trace element concentrations, generally at low background levels, are no higher and even reduced when dissolved methane is present. In addition, trace element concentrations are not correlated with distance to gas wells. The reduction in trace element concentrations is attributed to anaerobic microbial degradation of methane, is associated with a higher pH (>8.5), and, likely, with precipitation of carbonates and pyrite and formation of clays. Trace and other elements are likely incorporated within the precipitating mineral crystalline network or sorbed. High pH values are found throughout these high‐methane clusters (e.g., Parker‐Hood cluster), even in subregions where methane is not present, which is consistent with a pervasive natural origin of dissolved methane rather than a limited gas well source. Abstract : Article impact statement : Groundwater with high dissolved methane is associated with higher pH and lower trace element concentrations.